Unraveling hematopoietic stem cell ontogeny through single-cell multi-omics approaches - Jia, Yan; Huo, Sixuan; Wu, Fei; Song, Ningning; Li, Mei (Frontiers in Cell and Developmental Biology, 2025)
Definitive hematopoietic stem cells (HSCs) originate de novo within the vertebrate aorta-gonad-mesonephros (AGM) region via endothelial-to-hematopoietic transition (EHT) from hemogenic endothelial cells (HECs). The application of single-cell multi-omics has significantly deepened our knowledge about hematopoietic development. In this review, we focus on the ontogeny of HSCs and summarize novel insights gained from single-cell omics studies. These include newly identified components of hematopoietic regulatory networks, the cellular heterogeneity during HSC generation, innovative strategies for enriching rare cell subpopulations, and newfound knowledge about the AGM microenvironment. In the concluding section, we discuss key unresolved questions related to in vivo generation and in vitro induction of HSCs, while exploring the potential of single-cell omics to propel future research in this field.